The Influence of the Interpersonal Communication, Work Motivation, and Compensation of Teachers Toward the Performance of Elementary School Teachers in Magelang City - Syaebani, Tohar Latief (2011)
The objectives of this study are to describe (1) the interpersonal communication and performance of teachers; (2) the work motivation and performance of teachers; (3) compensation with teachers' performance; and (4) the interpersonal communication and work motivation of teachers jointly with teachers' performance in all Elementary School at Magelang City. It is a qualitative research ex post facto. This research will be conducted at Elementary School in Magelang. Researchers conducted a study in elementary schools in Magelang because previous researchers feel there is no research on elementary school in Magelang under the title Influence Personal Communication between Teachers, Teacher Work Motivation, and Compensation with Performance of Primary School Teachers Magelang. The population of this research was all Elementary School teachers in Magelang city amounting to 2304 teachers so the sample was 576 teachers. The sampling in this research was using proportional random sampling. The data collection method used enclosed questionnaire. Data analysis technique used multiple regression analysis. The results of this study are (1) Interpersonal communication thitung values obtained 5.874> 1.984 (p = 0.000) so as to have a positive and significant effect on the performance of elementary school teachers in Magelang; (2) Work motivation value obtained thitung 5.874> 1.984 (p = 0.000) so as to have a positive and significant effect on the performance of elementary school teachers in Magelang; (3) Compensation earned value thitung 6.681> 1.984 (p = 0.000) so as to have a positive and significant effect on the performance of elementary school teachers in Magelang; and (4) The result of calculations simultaneously is obtained Fcount of 114.548 > 2.60 so that the compensation, interpersonal communication and motivation to work together have a positive and significant impact on the performance of Elementary School teachers in Magelang.